Social and economical development strategies and principles of Khromtau city as a monocity (Journal of Geography and Environmental Management, 2016)
This article considers the development of Khromtau city as a monocity. The location of this monocity, which is in the regions of extracting of mineral resources, and its population, industry, development strategies and principles, as well as factors of social and economical development are discussed in this paper.
Keywords: one-industry town; monospetsializatsiya